Neutrophil Lymphocyte Ratio, Three Year Survival of Locally Advanced and Advanced Nasopharyngeal Carcinoma - Rahmat Cahyanur; Hayatun Nufus; Cosphiadi Irawan (Jurnal Penyakit Dalam Indonesia)
Introduction. Nasopharyngeal carcinoma (NPC) is the most prevalent head and neck malignancy in Indonesia, as NPC-related mortality in Indonesia is the second-highest in Asia after China. Inflammation has been studied to be associated with cancer progression. Neutrophil lymphocyte ratio describes the balance between the unfavorable suppression of immune response against cancer by neutrophils and the beneficial effect of adaptive immunity by lymphocytes. This study aimed to determine the relationship between NLR and the survival of locally advanced and advanced NPC patients.